The Impact of Disclosure Quality on Corporate Governance and Earnings Management: Evidence from Companies in Indonesia - Jatiningrum, Citrawati; Abdul-Hamid, Mohamad Ali; Popoola, Oluwatoyin Muse Johnson (International Journal of Economics and Financial Issues, 2016)
This paper investigates the relationship between corporate governance and earnings management with disclosure quality as a moderating variable in the scenario of highly concentrated ownership and less protected investors. The data obtain from listed Indonesian manufacturing companies using Moderated Regression Analysis (MRA) method complete the analysis of the interaction effects. The results reveal a significant effect of disclosure quality on the relationship between corporate governance mechanisms and earnings management. This study shows that disclosure quality and good corporate governance can reduce earnings management manipulation. The results are expected to contribute significantly to the existing knowledge on the concentrated ownership among companies on corporate governance, disclosure quality, and earnings management. Also, the findings will assist policy makers and regulators to facilitate directions for manufacturing sector and their operations in the future. Keywords: Disclosure quality, Corporate Governance, Earnings Management, Developing country JEL Classifications: M40, M41, M49